A method for local tuning of fuzzy membership functions - Çinar, A (Springer-Verlag Berlin, 2005)
In this paper, a new method based on genetic algorithms is proposed for local tuning of fuzzy membership functions. For this purpose, the local adjustment is employed on the initial membership functions. Genetic algorithm is used to investigate discrete points that will be modified on the membership functions Hence, global adjustment does not require and the processing time required for tuning of membership functions is decreased.
5th International Conference on Computational Science (ICCS 2005) -- MAY 22-25, 2005 -- Atlanta, GA